The role of networking in building a start-up business model - Ropuszyńska-Surma, Edyta; Węglarz, Magdalena; Kubiński, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The aim of this paper is two-fold. It focuses on the identification of crucial elements of the business model for the development of start-ups and for their potential to create innovation, as well as the influence of network cooperation on the components of their business model. The canvas model is used to illustrate the research outputs. Additionally, the research aimed at identifying what start-ups expect from the networks in which they exist (e.g., technological parks) in terms of creating appropriate conditions supporting innovations. The study was done using three expert panels in which 28 start-ups participated. The research and its results are qualitative and are presented as a case study. The research was conducted by the authors in 2019 and concerns start-ups participating in cooperation networks, but its results could be interesting not only for start-ups, but also for everyone interested in the issues of cooperation between various entities and its potential to stimulate innovation.
Keywords: business model (BM); canvas model; cooperation network; start-up; innovation